PENGELOLAAN KEUANGAN MASJID SEBAGAI ORGANISASI NIRLABA - Kusumadyahdewi, Kusumadyahdewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The mosque is a non-profit institution, which organizes many religious, social, educational and da'wah activities. The activities held to depend on a lot of funds obtained from the community as a source of mosque funding. Based on the results of the study, the sources of mosque funding were obtained from charity boxes attached to the walls of the mosque consisting of the construction of mosques, infaq of mosques, those entitled to receive, orphans, and the poor. Also from the charity box during Friday prayers, regular and non-permanent donors. Based on the money obtained, the mosque held social activities, education, and da'wah. As the manager's responsibility to the public, monthly income and expenditure reports are always posted on the mosque's bulletin board so that all can see the report. Besides, it also sends special financial reports to regular donors. This financial transparency makes it easier for mosques to raise funds from the public. The preparation of the mosque's financial report involves the treasurer and daily staff, as is known by the chairman of the mosque's takmir as the person in charge. As a community organization, this mosque is also monitored directly by the public by publishing its financial statements.Keywords: mosque; religion; social; education; da'wah